Agama dan kekerasan anti-Cina pada masa transisi demokrasi Indonesia, 1997-2004 - Laila Kholid Alfirdaus (Faculty of Social and Political Science, Universitas Airlangga, 2015)
In the discussions of anti-Chinese phenomena in Indonesian transition in 1997-2004, religion appears less dominating in regard of economic and political factors of ethnicity. In scientific works, the perception of antiChinese violence was also dominated by the views of politics and economy. In fact, religion also plays crucial role in many cases, ranging from the issue of Chinese infidelity, anti-Islamism and atheism. This is not to argue that politics, economy and social is not important. Otherwise, this paper argues that religion is equally important as politic, economic and social analysis, especially to explain anti-Chinese violence in Indonesia.